ANALISIS PENYALURAN RASKIN DI KOTA SEMARANG - eko, Rosiana; tatik, widiharih (MATEMATIKA, 2009)
Raskin Program is national program with aim to support impecunious household in fulfilling sufficiency of requirement of food and lessen burden of finansial through readying of rice subsidize. BPS have specified 14 ( fourteen) impecunious family criterion which become base of division of raskin. Household told impecunious if fulfilling one of the impecunious criterion. To analyze distributing of raskin conserning to the number of variable which is used in determining household receiver of raskin by logistics regression. Household owning highest probability accept raskin is household with floor is earth, residence wall type is bamboo, usage of facility defecate public, source of improtected wellspring drinking water, fuel to cook firewood, not capable to pay [for] the expense of medication, revenue of earnings of family head less than Rp 600.000,00 highest education of family head is Madrasah Ibtidaiyah, owning things which can be sold for the price of less than Rp 500.000,00 Â